Мultifunctional Inhibitors of "INCORGAZ" and "AMDOR" Series against Hydrosulfide and Carbon Dioxide Corrosion of Steel - Tsygankova, L.E.; Uryadnikova, M.N.; Shel, N.V.; Kostyakova, A.A. (Journal of Applied Solution Chemistry and Modeling, 2022)
Protective efficiency of inhibitors of the "INCORGAZ" and "AMDOR" series is analyzed in relation to carbon steel corrosion in model stratum waters of oil and gas fields saturated with hydrogen sulfide and carbon dioxide separately and together. The bactericidal properties of the inhibitors with respect to sulfate-reducing bacteria, reduction of steel hydrogenation, influence on the preservation of metal plastic properties are evaluated. The contributions of the inhibitor and the shielding film of corrosion products to the total protective effect are considered. The inhibitors under study provide a decrease in the corrosion rate of carbon steel to a value much less than 0.05 mm/year, according to the data of 240-hour exposure in hydrogen sulfide environments.